2018
DOI: 10.1016/j.gore.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian microcystic stromal tumor: Radiologic-pathologic correlation

Abstract: Ovarian microcystic stromal tumor (MST) is characterized by microcysts, solid cellular regions with lobulated growth, and collagenous or fibrous stroma forming hyaline plaques. While several reports have evaluated the unique pathologic and immunohistochemical profile of these tumors, there has been limited description of the radiologic findings of ovarian microcystic stromal tumor in the literature. We present a case of a 66 year old female who presented for evaluation of a new cystic pelvic mass found to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Microcystic stromal tumors of the ovary are also very rare tumors with favorable clinical course. A few case reports describe them as unilateral predominantly cystic masses with solid components that demonstrate mild FDG activity on PET/CT [53,54]. The cystic component appears as fluid density on CT, anechoic on US and hyperintense on T2-weighted MR images [54].…”
Section: Signet-ring Stromal Tumor and Microcystic Stromal Tumormentioning
confidence: 99%
See 2 more Smart Citations
“…Microcystic stromal tumors of the ovary are also very rare tumors with favorable clinical course. A few case reports describe them as unilateral predominantly cystic masses with solid components that demonstrate mild FDG activity on PET/CT [53,54]. The cystic component appears as fluid density on CT, anechoic on US and hyperintense on T2-weighted MR images [54].…”
Section: Signet-ring Stromal Tumor and Microcystic Stromal Tumormentioning
confidence: 99%
“…A few case reports describe them as unilateral predominantly cystic masses with solid components that demonstrate mild FDG activity on PET/CT [53,54]. The cystic component appears as fluid density on CT, anechoic on US and hyperintense on T2-weighted MR images [54]. Although, the imaging features are nonspecific and can be seen in malignant epithelial tumors, malignant potential has not yet been associated with microcystic stromal tumors [54].…”
Section: Signet-ring Stromal Tumor and Microcystic Stromal Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…Микрокистозная стромальная опухоль яичниковсолидная или кистозная гормонально неактивная опухоль, для которой свойственно наличие мелких кистозных полостей, которые изолированно или слитно расположены среди опухолевых клеток. Данная опухоль достаточно слабо изучена; известно, что встречается она главным образом у женщин пожилого возраста и характеризуется низкой пролиферативной активностью [12].…”
Section: Introductionunclassified
“…The incidence is second only to cervical cancer and endometrial cancer, with the highest mortality. 1,2 With the development in medical imaging, magnetic resonance imaging (MRI) has been used gradually in the diagnosis of ovarian diseases. Nishio et al found that the MRI findings, which suggested malignant transformation, were emergence of a solid portion and increase in cyst size.…”
Section: Introductionmentioning
confidence: 99%